How to Commercialize GETbizz : the new Database Marketing Platform Solution - Saraiva, Marta Machado de Almeida Garcia (2017)
Engaging in Customer Relationship Management practices is crucial in today’s business world. Strengthening business relations with clients and increasing customer loyalty are ones of companies´ priorities. GETbizz is a software that enables such practices by managing final clients’ database, establishing automated and personalized communications via SMS and email and even measuring the Return On Investment (ROI) of marketing campaigns. The present dissertation aims to reveal which could be the best commercialization strategy for GETbizz and its implementation on the market. With the purpose of understanding the software industry and analyzing the best recommendations for the launch of GETbizz, a benchmark was performed on this market. Furthermore, questionnaires to both current and potential clients’ of GETbizz were conducted so that the recommendations to the company were aligned with the targeted customer. Lastly, interviews with three different experts from renowned companies had taken place in order to get some industry’s insights. To successfully implement GETbizz in the market it seemed crucial to design structured segmentation, commercialization, pricing and placement approaches and the present thesis aims to unveil such strategies.